Signal transduction with a swing - Cash, Kevin J. (Nat Chem, 2021)
The continuous monitoring of proteins is a current challenge in medical diagnostics. A new electrochemical approach aiming to address this has been described. The method uses antibodies as a recognition element to achieve the real-time measurement of proteins in saliva in the mouth.